Analisa Kebutuhan Parkir - Edito Dwiantoro (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2015)
With the increasing number of vehicle users in Bengkulu City View Tower, the Tower View should provide a large parking area to accommodate the existing vehicle. If the vehicle parking problem needs not addressed, it can lead to kesemerawutan in the neighborhood, of course, this can interfere with existing teaching and learning. The purpose of this research is to evaluate the characteristics of the park (accumulation, volume, turnover rate, and parking index), as well as the needs of vehicle parking spaces View Tower in the city of Bengkulu. The research method is a survey of parking duration that is the way to record the number and timing of vehicles entering and exiting the parking area View Tower City of Bengkulu, the main reference used for parking survey redacted from the Directorate General of Land Transportation's decision No. 72 / Hk.105 / DJRD / 98 planning and operator of parking facilities. The study was conducted over two days, namely: Saturday, May 2, 2015, Sunday, May 3, 2015, Saturday, May 9, 2015 and Sunday, May 10, 2015 from 08: 00-14: 00 pm. Based on the results of the survey and data analysis parking maximum volume occurred on Sunday, May 3, 2015. Accumulated maximum parking occurs on a day Saturday, May 2, 2015 car parking areas as many as 13 vehicles / 60 minutes, and the motorcycle parking area Sunday, May 3, 2015 as many as 47 vehicles / 60 minutes. The level of turnover occurs daily maximum parking car parking area as much as 2 vehicles / day / room, and Sunday, May 3, 2015 IRD motorcycle parking area as much as 2 vehicles / day / room. Maximum parking index occurred on Sunday, May 3, 2015, namely: the car parking area 100%, and 99.11% motorcycle parking area. Parking space requirements, namely: the accumulated maximum of 112 SRP on Sunday, May 3rd, while capacity is as much as 113 SRP, accumulated maximum of 17 SRP on Saturday May 2, Sunday, May 3 and Sunday, May 10, while capacity is as much as 17 SRP. Based on the evaluation of the facility View Tower parking space Bengkulu city, it can be concluded that the capacity of the car park and bike during rush hour is still insufficient.